S85 Initiation of long-term non-invasive ventilation enables successful weaning from prolonged mechanical ventilation. (14th November 2013) - Parker, R; Sunderland, G; Ford, V; Ward, K; Ashcroft, H; Molyneux, V; Cheney, J; Chakrabarti, B; O'Reilly, J; Duffy, N; Angus, R
Abstract : Introduction: Prolonged mechanical ventilation is an increasing workload for intensive care units (ICU). Units distinct from ICU can provide step-down care for stable slow-to-wean patients and facilitate weaning by the use of long-term non-invasive ventilation (NIV). Development has been limited in the UK despite being recommended by the NHS Modernisation Agency in 2002 and reiterated by the NHS Commissioning Board in 2013. A unit opened at our hospital in September 2010 as part of a comprehensive complex home ventilation service. Methods: Review of completed in-patient episodes of transfers for weaning from invasive mechanical ventilation (IMV) from September 2010 to December 2012. Transfers following neurosurgery were compared with allcomers. Results: Thirty-nine patients were identified, mean age 54.2 (17.9) years, 24 male. Average length of stay (LOS) on the referring ICU was 49 days. Six had neuromuscular disease, nine COPD, 7 were obese or had chest wall disease, 14 ICU-acquired weakness and 3 used NIV prior to ICU admission. Thirty-five patients survived to hospital discharge. Thirty-one patients were successfully decannulated and weaned from IMV, including the use of nocturnal NIV. Twelve required no ventilatory support, 19 were discharged using nocturnal NIV and 5 continued nocturnal IMV (one of own choice). Twenty-two were discharged directly home, 7 to rehabilitation or the referring hospital and 6 to long-term nursing care. Thirty-four patients were alive 6 months after hospital discharge. Seven transfers had undergone neurosurgery, five having posterior fossa surgery. Compared with allcomers they were significantly more likely to have permanent bulbar dysfunction, require feeding gastrostomy, tracheostomy on discharge, have a longer LOS (106 vs 51 days) and were less likely to be discharged home. Long-term NIV was used in two neurosurgical patients compared with 17 allcomers. Conclusions: Patients with weaning failure can be effectively managed outside ICU. NIV enabled weaning in 50% of cases; consistent with published experience 1 . Six month survival is good and most are discharged directly home. Patients after neurosurgery present a specific challenge. NIV may not possible, and ongoing bulbar dysfunction may necessitate the retention of a tracheostomy for ventilation, airway protection and suction. References: Pilcher et al. Thorax 2005:187–192.